WorldCat Discovery - making European libraries more visible on the web - Lees, Janet (LIBER Quarterly: The Journal of the Association of European Research Libraries, 2006)
Firstly may I thank Trix Bakker and the Collection Development Division for inviting me to participate in their session today. I’m going to address the issue of making library collections more visible on the web and in particular the OCLC Open WorldCat program, the recent European enhancements to this program and the pilot that is currently underway.